Peran Ayah terhadap Status Gizi Anak Balita - Prisca A Tahapary; Siti Chodidjah; Imami Nur Rachmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the influence of the father's role in fulfilling the nutritional status of children. The method used is a systematic review based on guidelines from Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA), which includes e-resources from Science Direct, Scopus, Clinical Key Nursing, Sage Journal, Embase, Proquest from 2012 - 2022. The article included in this systematic review was based on the Population Intervention Comparison Outcome Study (PICOS) with a design for (P) all children aged 0-5 years, (I) the role of the father, (C) There was no comparative intervention, and (O) the child's nutritional status Good. The research results showed that eight articles were reviewed and that father involvement could improve children's nutritional status. In conclusion, the father's role in child care influences the child's nutritional status. Keywords: Children, Nutrition, Father's Role